2020
DOI: 10.1190/geo2019-0643.1
|View full text |Cite
|
Sign up to set email alerts
|

Frequency-dependent spherical-wave reflection coefficient inversion in acoustic media: Theory to practice

Abstract: As an approximation of the spherical-wave reflection coefficient (SRC), the plane-wave reflection coefficient does not fully describe the reflection phenomenon of a seismic wave generated by a point source. The applications of SRC to improve analyses of seismic data have also been studied. However, most of the studies focus on the time-domain SRC and its benefit to using the long-offset information instead of the dependency of SRC on frequency. Consequently, we have investigated and accounted for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…When the external force acts on the surface of the specimen, the elastic wave diffuses in the form of spherical wave in the specimen, causing vibration of each particle. 38 Thus, resulting in displacement signals, which can be collected by the AE sensor. The specimen thickness used in this experiment is only 30 mm, and the sensors were arranged on a narrow surface, as shown in Figure 1 .…”
Section: Methodsmentioning
confidence: 99%
“…When the external force acts on the surface of the specimen, the elastic wave diffuses in the form of spherical wave in the specimen, causing vibration of each particle. 38 Thus, resulting in displacement signals, which can be collected by the AE sensor. The specimen thickness used in this experiment is only 30 mm, and the sensors were arranged on a narrow surface, as shown in Figure 1 .…”
Section: Methodsmentioning
confidence: 99%
“…Harrison & Nielsen (2004) have shown that plane-wave reflection coefficients and spherical-wave reflection coefficients are related by a Hankel transform. AVO and data inversion using spherical-wave reflection coefficients have been demonstrated successful (Alhussain et al, 2008;Zhu & McMechan, 2015;Yan et al, 2020). However, it has to be remembered that, although they are largely used in common AVO/AVA studies, plane-wave reflection coefficients and spherical-wave reflection coefficients are strictly valid only for plane reflectors.…”
mentioning
confidence: 99%